Papers on Soils 1959 Meetings 1960
DOI: 10.1520/stp44323s
|View full text |Cite
|
Sign up to set email alerts
|

Improved Determination of Preconsolidation Pressure of a Sensitive Clay

Abstract: Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1968
1968
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 7 publications
1
28
0
Order By: Relevance
“…11 has very good agreements so it seems that throughout slow CRS tests flow rule is Non-Darcy. This is may be an answer to why researchers didn't obtain correct results from slow CRS test and standards had to define a minimum bound for relative pore pressure [4,2,16] , Since their used relation based on Darcy flow rule.…”
Section: The Boundary Of Darcy and Non-darcymentioning
confidence: 99%
“…11 has very good agreements so it seems that throughout slow CRS tests flow rule is Non-Darcy. This is may be an answer to why researchers didn't obtain correct results from slow CRS test and standards had to define a minimum bound for relative pore pressure [4,2,16] , Since their used relation based on Darcy flow rule.…”
Section: The Boundary Of Darcy and Non-darcymentioning
confidence: 99%
“…Hcducing the size of the load increment ixovides a curve from which a better estimate of the preconsoliclation pressure may be made, but the end of primary compression as determined by a curvefitting operation becomes less dcfinitc and results in less reliable time-compression predictions. The size of the increment ratio appears to have no effect on tlie total amount of compression for a given prcssure increment in the virgin compression range, provided the method of terminating load increments is bascd on a selected creep rate as already discussed (Hamilton and Crawford 1959). More recent research h.as shown that when load increments are not terminated on a creep rate basis, the pressure void ratio can be affected by the duration of the tests (Crawford 1964).…”
Section: Compressibilitymentioning
confidence: 99%
“…Printed in Cnnatla the effects of disturbing the structure of this sensitive clay. Laboratory investigations, such as reported by Hamilton and Crawford (1959) and by Crawford (1964), have shown that testing technique can have a great influence on the measured preconsolidation pressure. Final evaluation of these variables must, however, be made from field studies.…”
mentioning
confidence: 98%
“…The normal procedure of loading in small increments was used, with some refinements concerning (a) terminating load increments (Hamilton and Crawford 1959;Crawford 1964); (b) simulating field stress changes, as suggested by Skempton and Bjerrum (1957); and (c) loading just short of preconsolidation stress, releasing to overburdell stress and reloading, all in small load increments.…”
Section: Consolidation Testsmentioning
confidence: 99%